2015
DOI: 10.1007/s00268-015-3358-0
|View full text |Cite
|
Sign up to set email alerts
|

Morbid Obesity is Associated with Increased Mortality, Surgical Complications, and Incremental Health Care Utilization in the Peri‐Operative Period of Colorectal Cancer Surgery

Abstract: Analysis of national level data demonstrates that morbidly obese patients have an increased CRC surgery peri-operative mortality with higher prevalence of co-morbidities, surgical complications, and more health care resource utilization. Future research efforts should concentrate on ameliorating these outcomes in morbidly obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 37 publications
1
47
0
1
Order By: Relevance
“…Anastomotic leak of a gastrointestinal and/or pancreatic/biliary anastomosis was examined in 63 (53.4%) studies (Table ) . Among the studies that specifically considered this outcome, only 13 (20.6%) noted a higher incidence of anastomotic leak among obese patients . In studies that examined only patients with enteric anastomoses ( n = 52), the incidence of anastomotic leak was noted to be no higher among obese patients in 10 (19.2%) studies .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Anastomotic leak of a gastrointestinal and/or pancreatic/biliary anastomosis was examined in 63 (53.4%) studies (Table ) . Among the studies that specifically considered this outcome, only 13 (20.6%) noted a higher incidence of anastomotic leak among obese patients . In studies that examined only patients with enteric anastomoses ( n = 52), the incidence of anastomotic leak was noted to be no higher among obese patients in 10 (19.2%) studies .…”
Section: Resultsmentioning
confidence: 98%
“…Overall operative time was included in the majority of studies and was the only reported outcome that was associated with obesity in a majority of publications (Table ) . Among the 70 studies that included operative time as an outcome metric, 42 (60%) reported that obesity was associated with a longer operative time …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiologic data strongly support the observation that people with metabolic syndrome are at increased risk of colorectal adenoma and cancer 15, 16. Mortality due to colon cancer and obesity is greatly influenced by both genetic and environmental etiologic factors 17. Adipokines may play a crucial role in linking these two diseases 18, 19.…”
Section: Introductionmentioning
confidence: 81%